Menembus Batas Teks: Analisis Psikososial Terhadap Narasi Hadis Tentang Transgender - Zahrotul Izzah (Journal of Hadith Studies, 2025)
The study of transgender in Islam still leaves an academic gap, especially in looking at hadith texts in a contextual and interdisciplinary way. The dominant approach so far tends to be textual and normative, so it has not been able to fully answer the complexity of the social reality faced by transgender individuals. This study aims to explore the representation of transgender individuals in the Prophet's hadith through three main terms, namely mukhannath, mutarajjilah, and khunthāʾ, using a social psychology approach. The method used is a library research that analyzes primary hadith books and social psychology literature to understand the relationship between hadith texts and the formation of gender identity in society. The results of the study show that hadiths about transgender have a complexity of meaning that cannot be simplified in the dichotomy of halal-haram or curse-not curse alone. The curse in the hadith is directed at mukhannath and mutarajjilah, who deliberately imitate the opposite sex. At the same time, khunthāʾ, who experiences ambiguous biological conditions, is not included in the object of cursing. The social psychology approach asserts that social stereotypes and internal processes of individuals from childhood often influence transgender behavior. In addition to the element of prohibition, the hadith also shows the existence of social protection for transgender people as creatures created by Allah SWT. This finding emphasizes the importance of contextual and cross-disciplinary reading of hadith so that religious interpretations can be more humane, solutive, and relevant to contemporary social reality.